2009 Asia and South Pacific Design Automation Conference 2009
DOI: 10.1109/aspdac.2009.4796518
|View full text |Cite
|
Sign up to set email alerts
|

Addressing thermal and power delivery bottlenecks in 3D circuits

Abstract: Abstract-The enhanced packing densities facilitated by 3D integrated circuit technology also has an unwanted side-effect, in the form of increasing the amount of current per unit footprint of the chip, as compared to a 2D design. This has ramifications on two critical issues: firstly, it means that more heat is generated per unit footprint, potentially leading to thermal problems, and secondly, more current must be supplied per package pin, leading to possible power delivery bottlenecks. This paper presents an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…For a 3D chip with a footprint size of 1cm 2 , we may have thousands of P/G I/Os for each die and millions of wire segments on the P/G grids in each die [2]. The enhanced packing densities facilitated by 3D integrated circuit technology also have an unwanted side-effect, in the form of increasing the amount of current per unit footprint of the chip, as compared to a 2D design [3]. From the experimental results it is observed that a single TSV failure could increase the maximum voltage variation up to 70% in nano-scale ICs [4].…”
Section: Introductionmentioning
confidence: 97%
“…For a 3D chip with a footprint size of 1cm 2 , we may have thousands of P/G I/Os for each die and millions of wire segments on the P/G grids in each die [2]. The enhanced packing densities facilitated by 3D integrated circuit technology also have an unwanted side-effect, in the form of increasing the amount of current per unit footprint of the chip, as compared to a 2D design [3]. From the experimental results it is observed that a single TSV failure could increase the maximum voltage variation up to 70% in nano-scale ICs [4].…”
Section: Introductionmentioning
confidence: 97%
“…Existing work mainly came from two research communities, i.e., electronic design automation (EDA) and computer architecture. In the context of EDA, a significant amount of research has been done in the areas of physical design (e.g., see [1,16,25]) and thermal analysis and management (e.g., see [13,23,54]). As pointed out in [5], architectural innovations will play an at least equally important role as EDA innovations in order to fully exploit the potential of 3D integration.…”
Section: Introductionmentioning
confidence: 99%
“…Sophisticated thermal management techniques have been developed to address potential problems [30]. Common techniques include (i) thermal-aware block placement to spread high-power blocks and (ii) insertion of thermal TSVs (or recently microfluidic channels) in order to increase the vertical (or horizontal) thermal conductivity of a 3D IC.…”
Section: B Thermal Managementmentioning
confidence: 99%